Towards Vision 2020 -Trends of Cataract Surgery in Melaka Hospital, A Malaysian Tertiary Center: 2007-2014 - Thevi, T.; Abas, A.L. (Kathmandu University Medical Journal, 2020)
Background Cataract surgery which is the only scientific method to treat cataracts has evolved from large incisions of intracapsular cataract excision to extracapsular cataract excision and now modern day phacoemulsification. Anaesthesia too has progressed from general anaesthesia to local and topical anaesthesia. A variety of intraocular lenses are available ranging from rigid to foldable, multifocal and toric. Day care surgeries are becoming the norm these days.Objective Cataract surgery has advanced with new techniques and modalities. We studied the trends of cataract surgery and outcomes over the years.Method We performed secondary data analysis (National Eye Database) of cataract surgery patients in Hospital Melaka (2007 - 2014).Result Most patients were 60-69 years (mean 65.0 years). Primary cataract rose (p0.05). More patients presented with Hypertension and Diabetes (p